Metabolomic and Transcriptomic Analyses Reveal That a MADS-Box Transcription Factor TDR4 Regulates Tomato Fruit Quality - Zhao, Xiaodan; Yuan, Xinyu; Chen, Sha; Fu, Da-Qi; Jiang, Cai-Zhong (Frontiers in Plant Science, 2019)
Tomato fruit ripening is a complex process that influences fruit quality, including nutritional value. Transcription factors play important roles in the regulation of the ripening process. In this study, we sought to elucidate the complex mechanism by which a MADS-box transcription factor TDR4 modulates tomato fruit ripening and affects fruit quality. Suppression of TDR4 gene expression using virus-induced gene silencing technology (VIGS) resulted in an orange pericarp phenotype. Transcriptomic analysis of TDR4-silenced fruit showed changes in the expression of genes involved in various metabolic pathways, including amino acid and flavonoid biosynthesis pathways. Metabolomic analysis showed that levels of several amino acids, such as phenylalanine and tyrosine, and organic acids were reduced in TDR4-silenced fruit, while α-tomatine accumulated in TAGL1-silenced fruit. Taken together, our RNA-seq and metabolomics analyses of TDR4-silenced fruit showed that TDR4 is involved in ripening and nutrient synthesis in tomato fruit and is therefore an important regulator of fruit quality.